أثر المقامات العربية في مقامات الإلوري : دراسة تحليلية The Influence of arabic maqāmāt on Al-Ilūri’s Maqāmāt: an analytical study (2019)
The gaugical nexus in accessing the state of influence in the Literary arts of any existing nations which succinctly manifested through the literary output of the writers, researchers or the collection of books produced in the society; had being a great concern of the scholars and the researchers over the years back, in order to investigate the level of this influence in the world literature -cum- writers. On this, it is very apparent that everything in the global world has influence over others, the influence of Maqamah genre in Arabic and foreign literary heritage could not be under-estimated, Thus, led to its total applausive by the scholars, having discovered its elegance and rhetorical extravagance in Arabic literary arts, they displayed their linguistic and intellectual prowess in producing their own Maqamah piece on Hamadhani’s style, whom regarded as the pioneer of Maqamah genre. Therefore, the thrust of this paper is to examine the influence of Maqamatu-1- Arabiyyah in Al-llory’s Maqamah: An Analytical discourse. Al-Ilory’s Maqamah is a new production and virgin work written by Sheikh Muhammad Awwal Abdul Salam known as Sahibul- Qur’an in the twenty- first Century. Before delving into the depth of discussion, the research will discuss the concept of Maqamah and its rationale in the Arabic literary heritage, the historical background of Sahibul-Qur’an and his contribution would be discussed. The researcher will exploit an analytical approach in examining how influence is Sahibul Qur’an with Maqamatu-l-Arabiyyah.